Holding company location: a Polish tax perspective - Jamroży, Marcin; Janiszewska, Magdalena; Łożykowski, Aleksander (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
This paper aims to present the size and structure of passive income payments, such as dividends, interest, royalty payments, and fees for intangible services, made by companies domiciled in Poland belonging to a multinational enterprises (MNE) group. The authors formulate a hypothesis that tax jurisdictions offering extensive legal and tax incentives for holding structures, in particular concerning the tax treatment of dividends and other withholding tax payments, are the preferred location of holding companies. A review of the literature and legal sources precedes empirical research. The empirical analysis shows that passive income flows, including dividends, interest, royalties, and fees for intangible services, which constitute the dominant type of payments to holding companies, are directed from Poland primarily to countries with tax and regulatory solutions that are friendly to holding companies, including in particular the so-called intra-EU tax havens, namely Luxembourg, Cyprus, the Netherlands, Malta and Ireland. Real trade with these countries is neither significant nor proportional to the scale of passive income.